Antioxidant metabolism variation associated with alkali-salt tolerance in thirty switchgrass (Panicum virgatum) lines - Hu, Guofu (PLoS One, 2018)
Soil salinization is a major factor limiting crop growth and development in many areas. Switchgrass (Panicum virgatum L.) is an important warm-season grass species used for biofuel production. The objective of this study was to investigate antioxidant metabolism, proline,and protein variation associated with alkali-salt tolerance among 30 switchgrass lines and identify metabolic markers for evaluating alkali-salt tolerance of switchgrass lines. The grass lines were transplanted into plastic pots containing fine sand. When the plants reached E5 developmental stage, they were subjected to either alkali-salt stress treatment (150 mM Na(+) and pH of 9.5) or control (no alkali-salt stress) for 20 d. The 30 switchgrass lines differed in alkali-salt tolerance as determined by the level of leaf malondialdehyde (MDA), antioxidant enzyme activity [(superoxide dismutase (SOD), catalase (CAT), ascorbate peroxidase (APX)], proline and protein. Alkali-salt stress increased MDA, proline, SOD, reduced CAT activity, but its effect on protein and APX varied depending on lines. Wide variations in the five parameters existed among the 30 lines. In general, the lines with higher CAT activity and lower proline content under alkali-salt stress had less MDA, exhibiting better alkali-salt tolerance. Among the five parameters, CAT can be considered as valuable metabolic markers for assessment of switchgrass tolerance to alkali-salt stress.